Antibody therapy for acute myeloid leukaemia. (10th December 2013) - Gasiorowski, Robin E.; Clark, Georgina J.; Bradstock, Kenneth; Hart, Derek N. J.
Summary Novel therapies with increased efficacy and decreased toxicity are desperately needed for the treatment of acute myeloid leukaemia (AML). The anti CD33 immunoconjugate, gemtuzumab ozogamicin (GO), was withdrawn with concerns over induction mortality and lack of efficacy. However a number of recent trials suggest that, particularly in AML with favourable cytogenetics, GO may improve overall survival. This data and the development of alternative novel monoclonal antibodies (mAb) have renewed interest in the area. Leukaemic stem cells (LSC) are identified as the subset of AML blasts that reproduces the leukaemic phenotype upon transplantation into immunosuppressed mice. AML relapse may be caused by chemoresistant LSC and this has refocused interest on identifying and targeting antigens specific for LSC. Several mAb have been developed that target LSC effectively in xenogeneic models but only a few have begun clinical evaluation. Antibody engineering may improve the activity of potential new therapeutics for AML. The encouraging results seen with bispecific T cell‐engaging mAb‐based molecules against CD19 in the treatment of B‐cell acute lymphobalstic leukaemia, highlight the potential efficacy of engineered antibodies in the treatment of acute leukaemia. Potent engineered mAb, possibly targeting novel LSC antigens, offer hope for improving the current poor prognosis for AML.